2002
DOI: 10.1002/1521-4141(200207)32:7<2021::aid-immu2021>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Th2 response induced following adoptive transfer of dendritic cells in prediabetic NOD mice

Abstract: We previously demonstrated that immunotherapy with dendritic cells (DC) prevented diabetes development in prediabetic NOD mice and that this effect was optimal when using a stimulatory DC population generated from bone marrow cells cultured with granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) and IL‐4. In this study, we have investigated the mechanism by which GM‐CSF‐ and IL‐4‐cultured DC prevent diabetes in prediabetic NOD mice. Histological analysis of pancreatic tissue from DC‐treated mice reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 62 publications
3
72
1
Order By: Relevance
“…In setting dominated by Th1/Th17 cells, the local cytokine profile will induce an isotype switch towards the human IgG 1 subclass [7,8], while Th2 cells will induce an isotype switch towards the human IgG 4 subclass [9]. Whether this actually may prevent type 1 diabetes or not will need to be further investigated in future studies, but promising results have been shown in NOD mice [10,11].…”
supporting
confidence: 89%
“…In setting dominated by Th1/Th17 cells, the local cytokine profile will induce an isotype switch towards the human IgG 1 subclass [7,8], while Th2 cells will induce an isotype switch towards the human IgG 4 subclass [9]. Whether this actually may prevent type 1 diabetes or not will need to be further investigated in future studies, but promising results have been shown in NOD mice [10,11].…”
supporting
confidence: 89%
“…Several mechanisms of action have been suggested in the past [6,7,35] for the effect of DC and/or IL-4 in NOD mice. We opted for a different approach, using microarray analysis, to get a broader picture of the impact of DC/IL-4 treatment on gene expression in targeted tissues.…”
Section: Dc/il-4 Treatment Normalizes Gene Expression In the Plnmentioning
confidence: 99%
“…After 3-5 days in culture, the cells were restimulated (5Â10 5 /ml) with anti-TCR and soluble anti-CD28 for 24 h. Supernatants were collected for determination of cytokine production by ELISA as reported [36]. The cells for RT-PCR of c-Maf, EMSA and ChIP were obtained from 5-day T cell differentiation cultures, in which cells were expanded on day 3 in the presence of respective cytokines and antibodies followed by restimulation with PMA and ionomycin for 5 h.…”
Section: In Vitro Th or Tc Cell Differentiationmentioning
confidence: 99%